2013
DOI: 10.1021/ed300371n
|View full text |Cite
|
Sign up to set email alerts
|

Development, Implementation, and Analysis of a National Survey of Faculty Goals for Undergraduate Chemistry Laboratory

Abstract: This work reports the development of a survey for laboratory goals in undergraduate chemistry, the analysis of reliable and valid data collected from a national survey of college chemistry faculty, and a synthesis of the findings. The study used a sequential exploratory mixed-methods design. Faculty goals for laboratory emerged across seven factors, four of whichresearch experience, group work, error analysis, and laboratory writingshowed significant differences by course type. Significant differences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(143 citation statements)
references
References 12 publications
3
140
0
Order By: Relevance
“…Survey questions were developed by the authors and reviewed by university curriculum personnel in order to verify the clarity of the questions and answers. The survey questions emerged from those aspects of a science laboratory experience that have been found to be important (American Association of Physics Teachers 1998; Bruck and Towns 2013;Dikmenli 2007;Woodfield et al 2005). Generally, the questions explored the usability of the online laboratory and the extent of the connection between the lab and the lecture.…”
Section: Survey Development and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Survey questions were developed by the authors and reviewed by university curriculum personnel in order to verify the clarity of the questions and answers. The survey questions emerged from those aspects of a science laboratory experience that have been found to be important (American Association of Physics Teachers 1998; Bruck and Towns 2013;Dikmenli 2007;Woodfield et al 2005). Generally, the questions explored the usability of the online laboratory and the extent of the connection between the lab and the lecture.…”
Section: Survey Development and Structurementioning
confidence: 99%
“…Goals for laboratory experiences have been published for the disciplines of biology, chemistry, and physics (American Association of Physics Teachers 1998; American Chemical Society 2011; Dikmenli 2007;Woodfield et al 2005), and there is agreement among these groups that faceto-face laboratory experiences reinforce the topics and concepts introduced in the lecture and foster critical thinking skills. Bruck and Towns (2013), in their national survey of undergraduate chemistry faculty, reported that both general and organic chemistry teachers believe that laboratory activities support the lecture content. Students concurrently enrolled in lecture and laboratory sections tend to have better learning outcomes and retention when compared to their lecture-only peers (Matz et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Our results indicate that faculty have two broad goals for the undergraduate chemistry curriculum. They want students to learn hands-on techniques (and know when it is appropriate to use them) and to improve their critical thinking skills.…”
Section: Faculty Goals For Laboratorymentioning
confidence: 71%
“…6 To address the gaps in the research that has been carried out in laboratory in 2005 we embarked with our collaborators on a research trajectory that would help us understand the goals that faculty and students have for laboratory. [7][8][9][10][11][12][13][14][15][16] The ultimate goal has been to describe the correspondence between the two and to shape and guide the laboratory curriculum in ways that would bring about a better correspondence.…”
Section: Role Of Laboratorymentioning
confidence: 99%
See 1 more Smart Citation